Cognitive Functions of Enumeration in Economic Discourse - Антонова, М. (Київський національний університет імені Тараса Шевченка, 2024)
Background.Investigation of linguistic means representing knowledge within the framework of cognitive linguistics pertains its relevance. Our study of enumeration is carried on the material of economic discourse. The functions of enumeration are established. Semantically enumeration constitutes of homogeneous and heterogeneous enumerative series. Homogeneous enumerative series in economic discourse are represented by the economic spheres of human activity, while heterogeneous enumerative series are characterised by penetration of other spheres of human activity to economy. Structurally enumeration in economic discourse consists of linear and hierarchical constituents. Linear enumerations have two or more elements in their structure. Hierarchical enumerative series comprise linear enumerations subdivided into subordinate enumerative series. The degree of isolation of the elements of enumerative series can vary. Thus, the elements can be separated by means of punctuation, namely by commas within sentences and dots in paragraphs, as well as by paragraphs themselves. Methods. The main research methods are discourse analysis, descriptive and contextual analysis. In addition, techniques of syntactic-semantic analysis are used to clarify the peculiarities of enumeration in economic discourse. Results. This study explores functions of enumeration as a means to structure and represent conceptual information in economic discourse. As a result cognitive functions of enumeration characterised by content-related and structuring features were established. Conclusions. Content-related functions of enumeration in economic discourse serve to explain, name, generalise, specify, contrast, conceptualise, reveal and describe ideas and notions, as well as, structuring functions are implemented by sequencing, systematisation, framing and categorisation of information.

Вступ. Дослідження мовних засобів репрезентації знань з позицій когнітивної лінгвістики не втрачає своєї актуальності. Перелічення нами досліджено на матеріалі економічного дискурсу та встановлено його функції. Семантично перелічення конституюється гомогенними і гетерогенними перелічувальними рядами. Гомогенні перелічувальні ряди в економічному дискурсі репрезентовано економічними сферами діяльності людини, натомість гетерогенні перелічувальні ряди характеризуються проникненням в економіку інших сфер діяльності людини. Структура перелічення в економічному дискурсі може бути лінійною та ієрархічною. Лінійні перелічувальні ряди у своїй структурі мають два і більше елементів ряду. Ієрархічні перелічувальні ряди представлено лінійними переліченнями, яким властиве розгалуження структури основного ряду на підрядний ряд або підрядні ряди. Рівень відокремлення елементів перелічувального ряду може різнитися, йдеться про відокремлення елементів засобами пунктуації, а саме комами у межах речень та крапками на рівні абзацу, а також самими абзацами. Методи. Основними методами дослідження є дискурс-аналіз, описовий та контекстуальний аналіз. Додатково залучено прийоми синтаксично-семантичного аналізу для з’ясування природи перелічення в економічному дискурсі. Результати. Цю розвідку присвячено дослідженню функцій перелічення як засобу структурування та репрезентації концептуальної інформації у економічному дискурсі. Унаслідок аналізу було виокремлено когнітивні функції перелічення, яким притаманні змістовні та структуруючі властивості.  Висновки. Змістовні функції перелічення в економічному дискурсі сприяють експлікуванню, називанню, узагальненню, конкретизації, протиставленню, концептуалізації, розкриттю сутності та опису ідей і понять, натомість структуруючі функції реалізуються впорядкуванням, систематизацією, фреймуванням та категоризацією інформації.
Когнітивні функції перелічення в економічному дискурсі
Keywords: economic discourse; cognitive linguistics; enumeration; homogeneous enumeration; heterogeneous enumeration; functions of enumeration; економічний дискурс; когнітивна лінгвістика; перелічення; гомогенне перелічення; гетерогенне перелічення; функції перелічення